2020
DOI: 10.1101/2020.07.24.219121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurodegeneration induces a developmental RNA processing program by calpain-mediated MBNL2 degradation

Abstract: The Muscleblind-like (MBNL) protein family plays an important role in regulating developmental RNA processing transition. Loss of MBNL2 function has been implicated in the neurodegeneration of myotonic dystrophy type 1 (DM1). However, the causal mechanism of neurodegeneration-induced MBNL2 loss of function remains elusive. Here, we show that neurodegenerative conditions including NMDAR-mediated excitotoxicity and dysregulated calcium homeostasis triggered nuclear translocation of calpain-2 resulting in MBNL2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The bacterial infections in this cohort study was five episodes only, which amounts 0.23 attack per 100 child per year, this proportion was far less than that found in other cohorts was 2.6 and 1.6 attacks per 100 child per year. [17,18] This disparities may be linked to demographic/ geographical dissimilarities, in addition to the restricted period of the study matched to other studies, Rahav et al [17] informed a substantial increasing of the infection rate over time, especially after 15 years, which is lengthier than period since establishing of thalassemia center in our locality. Sepsis was one of the substantial severe bacterial infection in this study (n=2, 40%), earlier studies [18,19] found less occurrence of septicemia (14-25%) because of variety of infections like liver abscess which was not seen in this study.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The bacterial infections in this cohort study was five episodes only, which amounts 0.23 attack per 100 child per year, this proportion was far less than that found in other cohorts was 2.6 and 1.6 attacks per 100 child per year. [17,18] This disparities may be linked to demographic/ geographical dissimilarities, in addition to the restricted period of the study matched to other studies, Rahav et al [17] informed a substantial increasing of the infection rate over time, especially after 15 years, which is lengthier than period since establishing of thalassemia center in our locality. Sepsis was one of the substantial severe bacterial infection in this study (n=2, 40%), earlier studies [18,19] found less occurrence of septicemia (14-25%) because of variety of infections like liver abscess which was not seen in this study.…”
Section: Discussionmentioning
confidence: 50%
“…[17,18] This disparities may be linked to demographic/ geographical dissimilarities, in addition to the restricted period of the study matched to other studies, Rahav et al [17] informed a substantial increasing of the infection rate over time, especially after 15 years, which is lengthier than period since establishing of thalassemia center in our locality. Sepsis was one of the substantial severe bacterial infection in this study (n=2, 40%), earlier studies [18,19] found less occurrence of septicemia (14-25%) because of variety of infections like liver abscess which was not seen in this study. Pneumonia comprised 20% of infections within the study, this was nearly consistent with previous studies 26% and 21.4% [17,19].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation